Human centered computing : Third International Conference, HCC 2017, Kazan, Russia, August 7-9, 2017, Revised selected papers /: Third International Conference, HCC 2017, Kazan, Russia, August 7-9, 2017, Revised selected papers. ([2018]) - Unknown
No abstract available